Implementasi Kepemimpinan Berbasis Nilai Pancasila dalam Penyelenggaraan Pemerintah Daerah - Oihu, Safardan. Ka; Gazalin, Junaid; Ferdiyansyah, Ferdiyansyah; Setiawan, Rismal; Sampe, Silas Adian (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Local government leadership in Indonesia faces complex challenges in implementing Pancasila values ​​as the basic philosophy of the nation and state. The era of globalization and socio-political transformation has created systemic pressure on the governance system, demanding adaptation of leadership philosophy that is able to respond to the dynamics of change while maintaining national identity. Pancasila is not just a historical document, but a living and sustainable ethical framework in the practice of regional government administration. This study aims to comprehensively analyze the implementation of Pancasila values ​​in local government leadership. Specifically, the study focuses on identifying the practice of implementing Pancasila values ​​in regional leadership, exploring supporting and inhibiting factors for the internalization of national values, analyzing the impact of implementing Pancasila values ​​on the quality of governance, and formulating leadership development strategies based on the noble values ​​of Pancasila. The research methodology uses a qualitative approach with a descriptive case study method. The location of the study was determined in the Central Java Provincial Government, considering the complexity of government characteristics and the representativeness of the dynamics of regional leadership in Indonesia. Data collection techniques were carried out through in-depth interviews with key informants, participatory observation, and analysis of official government documents. The selection of informants was carried out purposively, including regional heads, regional secretaries, heads of related agencies, community leaders, and academics who have experience and capacity in the field of government leadership. Data analysis used the Miles and Huberman interactive model, including the stages of data reduction, data presentation, verification, and drawing conclusions. The results of the study indicate that the implementation of Pancasila values ​​in regional government leadership still faces complex structural and cultural challenges. Despite various positive efforts, the internalization of Pancasila values ​​is often hampered by rigid bureaucratic practices, pragmatic interests, and limited in-depth understanding of the philosophical substance of Pancasila. The conclusion of the study confirms that the implementation of Pancasila values ​​in regional leadership is a dynamic process that requires total commitment from all components of government and society. Transformation cannot be done instantly, but through systemic, sustainable, and participatory efforts.